La Basilica del Santo Sepolcro a Gerusalemme: resoconto di una ricerca multidisciplinare - Grazia Tucci (mediaGEO soc. coop., 2020)
Jerusalem is located in a highly seismic area and has been the scene of disastrous earthquakes in the past. The 1927 earthquake was one of the worst that occurred in that area, as well as victims of victims, causing significant damage to the structures of civil and religious buildings. The Basilica of the Holy Sepulcher was also heavily hit and suffered, following the damage from that earthquake, major consolidation and reconstruction works. A study on the city of Jerusalem showed a periodicity, in the repetition of seismic events, of about 100 years. The desire to avoid an announced danger was the origin of the project described in the book "Jerusalem The Holy Sepulcher - Research and Investigation (2007-2011)" edited by the writer. In 2006 the three main communities of the Holy Sepulcher dealt with the Basilica's ability to withstand a new earthquake, a technical evaluation of its structures was required and required to plan a possible consolidation in relation to the results derived from the analyzes.